Estimating Ideal Sleep Duration by Physical Fitness in South Korean Adults: A Correlational Epidemiological Study - Jong Hyeon Lee; Jae Min Lee; Hee Seong Jeong; Wi-Young So (SAGE Open, 2022)
This study aimed to verify the relationship between ideal sleep duration and physical fitness in South Korean adults and older adults. The secondary analysis data of 2,832 adults (19–64 years) and 629 older adults (65 years and above), obtained from the 2015 National Fitness Survey, were analyzed. Participants completed various physical fitness tests (grip strength, sit-ups, standing long jump, 50 m dash, sit-and-reach, and 20 m shuttle run in adults; grip strength, sit-up, sit-to-stand, sit-and-reach, back-scratch, one-leg standing test, and 6-minute walk in older adults) and were divided into four groups based on self-reported sleep duration. Group differences in physical fitness variables were analyzed with one-way analysis of variance, and Pearson’s correlation was used to verify the relationship between sleep duration and physical fitness; statistical significance was set at p  < .05. In adult males, there was a positive correlation between explosive muscular strength (standing long jump) and sleep duration ( p  = .046), whereas in adult females, there was a negative correlation between cardiopulmonary endurance (20 m shuttle run) and sleep duration ( p = .026). However, in older adults, there was no significant correlation between sleep duration and physical fitness ( p  > .05). Further, across the sample, there were no significant group differences in physical fitness variables. A positive correlation exists between sleep duration and muscular strength in adult males and a negative correlation between sleep duration and cardiorespiratory endurance in adult females. Designing sleep and exercise programs based on these results may improve physical fitness among adults and older adults. Future studies that include controlled variables that affect physical fitness and sleep patterns are warranted.